1997
DOI: 10.1002/stem.150009
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobilized Peripheral Blood Stem Cells from Normal Donors for Allografting

Abstract: Peripheral blood stem cells (PBSCs) are gaining increasing acceptance as an alternative to bone-marrow (BM)-derived stem cells for allografting. Although scarce under steady-state conditions, CD34 + progenitor cells can be effectively mobilized into the peripheral blood (PB) in the vast majority of normal donors with a brief (3-4 days) course of recombinant human (rHu)G-CSF. Those cytokine-peripheralized progenitor cells and, among them, pluripotent stem cells, are collected by apheresis in sufficient amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 43 publications
(52 reference statements)
4
19
1
Order By: Relevance
“…The purity of the final product correlated with the number of CD34 + cells placed on the device and was not influenced by the total number of nucleated cells used for selection or the percentage of CD34 + cells recovered. These observations support efforts to improve CD34 + mobilization with agents such as stem cell factor 61,62 and flt3 ligand. 63 Our experience provides further evidence that G-CSF mobilization and apheresis are safe for normal adult donors.…”
Section: Discussionsupporting
confidence: 69%
“…The purity of the final product correlated with the number of CD34 + cells placed on the device and was not influenced by the total number of nucleated cells used for selection or the percentage of CD34 + cells recovered. These observations support efforts to improve CD34 + mobilization with agents such as stem cell factor 61,62 and flt3 ligand. 63 Our experience provides further evidence that G-CSF mobilization and apheresis are safe for normal adult donors.…”
Section: Discussionsupporting
confidence: 69%
“…30 In 1997, Anderlini & Körbling assumed a more primitive phenotype of CD34 + cells contained in PBSC compared with BM. 25 Furthermore, they postulated a faster engraftment after PBSC transplantation compared with BM allografting as described before. 26 This was later confirmed by different authors, who reported no differences in both overall and event-free survival between PBSC and BM, but observed a clearly faster neutrophil and platelet engraftment after infusion of PBSC.…”
Section: Discussionmentioning
confidence: 80%
“…This may be the reason for the more rapid sustained engraftment after infusion of PBSC instead of BM. 25,26 In BM1y, these earlier CD34 subtypes are again significantly lower than in BMd. In contrast, the more committed CD34 stages, that is, MLP and particularly BLP, are significantly higher in BM1y than in BMd, whereas they are hardly present in PBSC.…”
Section: Discussionmentioning
confidence: 87%
“…[6][7][8][9] As many patients receiving relatively small doses of CD34 þ cells show adequate engraftment, the importance of the composition of the PBPC allograft has received only limited attention. [10][11][12][13] The effect of the composition of the PBPC grafts from MRDs and from MUDs on hematologic recovery of the patents was studied, with particular attention to the differences between MRD and MUD grafts.…”
Section: Introductionmentioning
confidence: 99%